O cuidado de si e sua contribuição para uma docência amorosa - Anjos, Silvani Alves dos (2023)
We live in a society in which the weaknesses of human bonds are increasingly present, in a consumerist and individualistic culture, where our efforts are centered on the search for immediate satisfaction, and in this scenario, undertaking self-care actions requires a rescue of a way of life that values life. In this context, I realized the possibility of rethinking teaching and questioning what in me drove me to continue adopting a loving teaching practice, not to give up on who I am and what drives me. In an autobiographical narrative research proposal about my pedagogical practice, this study presents a reflection on how self-care can contribute to loving teaching. The concerns of my experience allowed me to move through the field of self-care and love in the experience with myself and with my students, dialoguing with Foucault, bell hooks, Bauman and Boff. Care of the self (epimeléia heautoû) needs to be understood as a way of life that leads to the formation of the subject by himself, knowing himself, taking care of himself and seeing love as an attribute of transformation of society. From the narratives of classroom situations, I concluded that the subject, when awakening to “self-care”, is moved to look inside and conceive that he is immersed in the relationships he establishes with himself and with others and, from there, you can change. In this way of thinking, I saw myself occupying a significant position in the student’s life and the school becoming a propitious space for, based on self-care, building and strengthening loving bonds in teaching.